Banks' Maturity Transformation : Risk, Reward, and Policy - Bologna, Pierluigi (IMF Working Papers; Working Paper ;, 2018)
The aim of this paper is twofold: first, to study the determinants of banks' net interest margin with a particular focus on the role of maturity transformation, using a new measure of maturity mismatch; second, to analyse the implications for banks from the relaxation of a binding prudential limit on maturity mismatch, in place in Italy until mid-2000s. The results show that maturity transformation is a relevant driver of the net interest margin, as higher maturity transformation is typically associated with higher net interest margin. However, 'excessive' maturity transformation- even without leading to systemic vulnerabilities- increases banks' interest rate risk exposure and lowers their net interest margin.